Archaean Intracrustal Differentiation from Partial Melting of Metagabbro-Field and Geochemical Evidence from the Central Region of the Lewisian Complex, NW Scotland - Johnson, Tim; Fischer, S.; White, R.; Brown, M.; Rollinson, H. (Oxford University Press, 2012)
The central region of the mainland Lewisian gneiss complex of NW Scotland is a granulite-facies migmatite terrane. With the exception of ultramafic and rare calc-silicate rocks, all other lithologies partially melted during Neoarchaean, ultrahigh-temperature (Badcallian) metamorphism. The clearest evidence is preserved within large layered mafic–ultramafic bodies that exhibit macroscopic features diagnostic of anatexis. In situ partial melting of metagabbroic rocks produced patches and sheets of coarse-grained plagioclase-rich leucosome containing euhedral peritectic clinopyroxene. These leucosomes connect with larger, laterally continuous tonalite or trondhjemite sheets that record segregation and migration of melt away from the metagabbro source rocks. This melt loss allowed wide-scale preservation of granulite-facies assemblages within the residual melanosome. Whole-rock major and trace element geochemistry is broadly consistent with the field evidence, but suggests contamination of the metagabbroic rocks by their host-rocks and a strong mineralogical control on trace element distributions, the consequence of large diffusive length scales during protracted ultrahigh-temperature metamorphism. Variations in the trace element composition of the felsic sheets reflect heterogeneities in the source rocks, the presence of material entrained from the melanosome and fractional crystallization dominated by plagioclase. The felsic sheets are largely cumulate, suggesting loss of the evolved melt fraction to higher crustal levels. Partial melting of felsic gneisses that surround the mafic–ultramafic bodies is inevitable at the implied metamorphic peak provided they contained hydrous phases, although the field evidence is largely obscured by later reworking. This study provides insights into the processes involved in intracrustal differentiation during the Neoarchaean, during which partial melting of mafic rocks is likely to have made a more significant contribution than during the Phanerozoic.